An updated review of the immunological mechanisms of keloid scars - Lee, Chih-Chun; Tsai, Chia-Hsuan; Chen, Chih-Hao; Yeh, Yuan-Chieh; Chung, Wen-Hung; Chen, Chun-Bing (Frontiers in Immunology, 2023)
Keloid is a type of disfiguring pathological scarring unique to human skin. The disorder is characterized by excessive collagen deposition. Immune cell infiltration is a hallmark of both normal and pathological tissue repair. However, the immunopathological mechanisms of keloid remain unclear. Recent studies have uncovered the pivotal role of both innate and adaptive immunity in modulating the aberrant behavior of keloid fibroblasts. Several novel therapeutics attempting to restore regulation of the immune microenvironment have shown variable efficacy. We review the current understanding of keloid immunopathogenesis and highlight the potential roles of immune pathway-specific therapeutics.